Caregivers’ knowledge and attitude scale towards drug: development and validation - Chaudhuri, Pamela Datta; Ray, Suvendu; Sikdar, Deb Prasad (International Journal of Research in Medical Sciences, 2023)
Background: Drug abuse is a prevalent issue in society, often used to reduce stress and improve mental health. It is often seen as a personal disorder, causing harm to users and their loved ones. In today’s globalized world, society strives for better care, emphasizing the importance of solving problems and emphasizing the role of caregivers in supporting drug addicts. Methods: A standardized knowledge and attitude scale was developed to assess 60 caregivers of drug addicts in Kolkata, India. The scale was self-administered and tested at 21-day intervals. The Pearson’s correlation coefficient method was applied for questionnaire validity. The scale was used to eliminate poor items and ensure reliability. Results: The tool primarily consists of twenty-two (22) knowledge and twenty-two (22) attitude items towards drug. Following item analysis, four (4) distracting items from the knowledge scale are dropped in accordance with the difficulty index and discrimination index. The discrimination indices from the attitude scale were used to eliminate 1 distracting item. As a result, 18 items for the knowledge scale and 21 items for the attitude scale were retained. The knowledge and attitude tools’ final form has found high significant correlation. Conclusions: The study explained how to create a standardized scale with good items and significant reliability to evaluate knowledge and attitude towards drug addicts.